Improved pulse‐width modulation scheme for T‐type multilevel inverter. Issue 8 (4th April 2017) - Vemuganti, Hari Priya; Sreenivasarao, Dharmavarapu; Siva Kumar, Ganjikunta
Abstract : In recent times, reduced switch count multilevel inverter (RSC‐MLI) has become an emerging area of research in power electronic converters. To control these RSC‐MLI topologies, various novel modulation schemes are reported. Multi‐reference is one of such modulation scheme reported for various RSC topologies, such as T‐type. However, the performance of this conventional scheme results in high total harmonic distortion (THD) in line voltages, when compared with the conventional level shifted pulse‐width modulation scheme. This observation is clearly presented in this study and the reason for its degraded THD performance has been deeply discussed. To alleviate this problem, a modified multi‐reference dual‐carrier modulation technique with multiple references and two carriers is proposed. To implement this proposed modulation technique, an alternate carrier and modulation signals arrangement with multiple carriers and single reference is also presented. Finally, a comparative THD performance of the proposed and conventional modulation schemes is carried out on a five‐level T‐type MLI and obtained simulation results are validated experimentally.